2006
DOI: 10.1038/sj.ejcn.1602463
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of resting energy expenditure in bronchopulmonary dysplasia to predicted equation

Abstract: Objective: Children with bronchopulmonary dysplasia (BPD) often suffer from growth failure because of disturbances in energy balance with an increase of resting energy expenditure (REE). Evaluation of REE is a useful tool for nutritional management. Indirect calorimetry is an elective method for measuring REE, but it is time consuming and requires rigorous procedure. The objective of this study was to test accuracy of prediction equation to evaluate REE in BPD children. Patients and methods: Fifty-two children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…2,26 They may also have increased frequency of respiratory infections in infancy 27 and have been reported to have increased arterial systolic blood pressure in childhood. 7 Furthermore, they have altered body composition 28 and _ VO 2 max, as expressed in terms of body mass, tends to be underestimated in heavier subjects and overestimated in lighter subjects. 29 Taken together, the increased risk factors leading to cardiorespiratory illness could potentially have an effect on these children's exercise capacity, especially those who developed BPD in infancy.…”
Section: Discussionmentioning
confidence: 99%
“…2,26 They may also have increased frequency of respiratory infections in infancy 27 and have been reported to have increased arterial systolic blood pressure in childhood. 7 Furthermore, they have altered body composition 28 and _ VO 2 max, as expressed in terms of body mass, tends to be underestimated in heavier subjects and overestimated in lighter subjects. 29 Taken together, the increased risk factors leading to cardiorespiratory illness could potentially have an effect on these children's exercise capacity, especially those who developed BPD in infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Suman et al studied the critically ill patient with burns, and also showed significant differences between measured and calculated EE as follows: IC vs. Schofield-HW (mean difference, −64.7 to −22.4 kcal/day); IC vs. Harris-Benedict (mean difference, 640 ± 555 kcal/day); and IC vs. Food and Agriculture Organization, World Health Organization, and the United Nations University (FAO/WHO/UNU) (mean difference, 652 ± 559 kcal/day) [126]. Bott et al reported similar results following a study that included 52 pediatric patients with bronchopulmonary dysplasia as follows: IC vs Harris-Benedict (mean difference, −15 ± 33.3); IC vs. Schofield-W (−51.3 to −2.0), Schofield-HW (−67.7 to −22.4); and IC vs. FAO/WHO/UNU (−47.5 to 7.4) [127,128].…”
Section: Nutritional Therapy Guided With Indirect Calorimetry In Critmentioning
confidence: 63%
“…Moreover, results are similarly conflicting in patients with different diseases. Bott et al showed that the HBE and Schofield equations showed best agreement with measured REE values in children with bronchopulmonary dysplasia and in healthy children, respectively 9. However, Suman et al reported that equations underestimated measured REE values, and that the Schofield equation produced results that were closer to measured REE values in children with severe burns 10.…”
Section: Discussionmentioning
confidence: 99%